Evaluation of the Energy Efficiency of the Stage Compression Heat Pump Cycle - S. K. Abildinova; R. A. Musabekov; A. S. Rasmukhametova; S. V. Chicherin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The increase in production and modernization of existing heat pumps are global trends in the development and implementation of heat pump technology. Application of refrigerant with zero potential ozone depletion relative to fluorinetrichloromethane and minimum values of global warming potentials relative to carbon dioxide is environmentally justified in pumps. Prospective are stage compression heat pump units and, also, consecutive and cascade schemes of inclusion which provide higher temperature of the heat carrier in the system of heat supply. Improving the efficiency of the heat pump depends on the perfection of the thermodynamic cycle, on the choice of the working agent and on the quality of the operation of the unit in off-design conditions of a temperature mode. The article presents the results of a study of the performance of stage compression heat pump. The concepts of application of the heat pump of two-stage compression of the working agent are formulated. Experimental researches has been fulfilled with the use of Altal GWHP26Н heat pump of 24.2 kW capacity operating on an eco-friendly refrigerants of R134a and R600а. The results of comparative calculation of performance indicators of one- and two-stage heat pumps are presented. Various schemes of realization of a thermodynamic cycle for one- and two-stage heat pumps are considered. The efficiency of two-stage heat pumps that implement thermodynamic cycle with supercooling of condensate and regeneration of steam heat of the working agent has been proved. The two-stage thermodynamic cycle of the heat pump is accompanied by minimal losses during the throttling of the liquid refrigerant, and it solves the problem of useful heat use to increase the temperature of the heated coolant for heating and hot water supply systems. Steam regeneration of the working agent at the outlet from the evaporator through the use of regenerative heat exchanger also provides the additional effect of minimization of thermodynamic losses and improving efficiency of cycles with vapor compression heat pumps in the conditions of large temperature differences in the evaporator and the condenser.